2019
DOI: 10.21802/acm.2019.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Variants of Localization and Extension of Hypo- and Aplasia of the Great Saphenous Vein in Patients with Primary Varicose Great Saphenous Veins

Abstract: The objective of the research was to improve the diagnostics and treatment of patients with primary varicose great saphenous veins by studying their frequency and systematizing the variants of localization and extension of great saphenous vein hypoplasia and aplasia in its trunk. Materials and Methods. The study included 560 patients with varicose veins of the lower limbs and pathological refluxes in different segments of the great saphenous vein. All the patients underwent triplex ultrasound scan of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In a study by Rostyslav Sabadosh in 560 limbs with varicose veins, hypoplasia was observed in 20.4% of cases and aplasia in 9.8% cases (Figure 4). 2
Figure 4.Duplex study showing partial duplication of great saphenous vein (GSV) in thigh. The two moieties are joining each other near SFJ and at lower third of thigh (B).
…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Rostyslav Sabadosh in 560 limbs with varicose veins, hypoplasia was observed in 20.4% of cases and aplasia in 9.8% cases (Figure 4). 2
Figure 4.Duplex study showing partial duplication of great saphenous vein (GSV) in thigh. The two moieties are joining each other near SFJ and at lower third of thigh (B).
…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of duplicated GSV is one of the common causes of residual or recurrent varicosities even after surgical or endovenous Embryologically corresponds to aplasia-vein is diminished in size and its structure is like that in embryo. 2…”
Section: Anomalies Of Gsvmentioning
confidence: 99%
See 1 more Smart Citation